AaPKAc Regulates Differentiation of Infection Structures Induced by Physicochemical Signals From Pear Fruit Cuticular Wax, Secondary Metabolism, and Pathogenicity of Alternaria alternata - Zhang, Miao; Li, Yongcai; Wang, Tiaolan; Bi, Yang; Li, Rong; Huang, Yi; Mao, Renyan; Jiang, Qianqian; Liu, Yongxiang; Prusky, Dov B. (Frontiers in Plant Science, 2021)
Alternaria alternata, the casual agent of black rot of pear fruit, can sense and respond to the physico-chemical cues from the host surface and form infection structures during infection. To evaluate the role of cyclic AMP-dependent protein kinase (cAMP-PKA) signaling in surface sensing of A. alternata, we isolated and functionally characterized the cyclic adenosine monophosphate dependent protein kinase A catalytic subunit gene (AaPKAc). Gene expression results showed that AaPKAc was strongly expressed during the early stages of appressorium formation on hydrophobic surfaces. Knockout mutants ΔAaPKAc were generated by replacing the target genes via homologous recombination events. We found that intracellular cAMP content increased but PKA content decreased in ΔAaPKAc mutant strain. Appressorium formation and infection hyphae were reduced in the ΔAaPKAc mutant strain and the ability of ΔAaPKAc mutant strain to recognize and respond to high hydrophobicity surfaces and different surface waxes was lower than in wild type (WT) strains. In comparison with WT strains, the appressorium formation rate of ΔAaPKAc mutant strain on high hydrophobicity and fruit wax extract surface was reduced by 31.6 % and 49.3% 4 h after incubation, respectively. In addition, AaPKAc is required for the hypha growth, biomass, pathogenicity and toxin production of A. alternata. However, AaPKAc negatively regulated conidia formation, melanin production and osmotic stress resistance. Collectively, AaPKAc is required for pre-penetration, developmental, physiological, and pathological processes in A. alternata.